Determinants of contraceptive use among Nigerian couples: evidence from the 2013 Demographic and Health Survey. Issue 1 (December 2017) - Blackstone, Sarah; Iwelunmor, Juliet
Abstract Background Nigeria remains a focus for increasing contraceptive use, as it is one of the most populous countries in Sub-Saharan Africa. The objective of the current study was to investigate determinants of contraceptive use in Nigeria couples. Methods Using the 2013 Nigeria Demographic and Health Survey, we estimated the likelihood of contraceptive use based on concordance with male partner desire for family size, male and female fertility preferences, female decision making power, and male partner attitudes toward contraceptive use. Results Male partner perception that decisions regarding health should be made jointly or primarily by women was positively associated with use. Women were less likely to use contraceptives in couples in which male partners had greater earning power. Finally, men who viewed contraceptives as an enabler for promiscuity had female partners less likely to use contraceptives. Conclusions These findings highlight the importance of male partners in women's contraceptive decision making.